Project Based Sukuk (PBS) and Its Implementation in Economic Development in Indonesia - Kurniawan, Taufiq; Rahman, Asmak Ab (Universitas Islam Negeri Raden Intan Lampung, 2019)
The Indonesian government needs funds to accelerate infrastructure development. Therefore, in 2012 Indonesia issued a PBS sukuk specifically to finance infrastructure development. This research was conducted to find out how the implementation of PBS sukuk in economic development in Indonesia is seen from the perspective of Islamic economics. Data was collected using interview and documentation methods from primary and secondary sources. The results of this study indicate that the issuance of PBS sukuk from time to time has shown significant growth. This is indicated by the PBS sukuk budget which is increasing from year to year in line with the increasing investor interest in the Shari'ah concept-used instrument. PBS's increasing budget in building national infrastructure also proves that Islamic instruments have grown in the capital market. So that it will gradually reduce the concept of usury circulating in the capital market. This phenomenon also shows that the Shari'ah economy has an important role in helping the government, especially in the field of infrastructure development.